On the power of autobiographical memories: from threat and challenge appraisals to actual behaviour. Issue 10 (25th November 2016) - Selimbegović, Leila; Régner, Isabelle; Huguet, Pascal; Chatard, Armand
ABSTRACT: Autobiographical memories are a major feature of mental life in humans. However, research on the influence of autobiographical recall on actual behaviour is scarce. We predicted and found that general memories of failure and specific memories of success resulted in worse performance than general memories of success and specific memories of failure. This performance pattern was mediated by task appraisal, suggesting that autobiographical memories (of failure and success) impact performance by shaping the perception of the upcoming task. Combined with the fact that these effects occurred even when the content of autobiographical memories was unrelated to the upcoming task, the present research represents an important step forward in understanding how autobiographical recall influences actual behaviour.